Evolutionary relationships among cyanobacteria and green chloroplasts. - Giovannoni, S J (1988)
The 16S rRNAs from 29 cyanobacteria and the cyanelle of the phytoflagellate Cyanophora paradoxa were partially sequenced by a dideoxynucleotide-terminated, primer extension method. A least-squares distance matrix analysis was used to infer phylogenetic trees that include green chloroplasts (those of euglenoids, green algae, and higher plants). The results indicate that many diverse forms of cyanobacteria diverged within a short span of evolutionary distance. Evolutionary depth within the surveyed cyanobacteria is substantially less than that separating the major eubacterial taxa, as though cyanobacterial diversification occurred significantly after the appearance of the major eubacterial groups. Three of the five taxonomic sections defined by Rippka et al. (R. Rippka, J. Deruelles, J. B. Waterbury, M. Herdman, and R. Y. Stanier, J. Gen. Microbiol. 111:1-61, 1979) (sections II [pleurocapsalean], IV [heterocystous, filamentous, nonbranching], and V [heterocystous, filamentous, branching]) are phylogenetically coherent. However, the other two sections (I [unicellular] and III [nonheterocystous, filamentous]) are intermixed and hence are not natural groupings. Our results not only support the conclusion of previous workers that the cyanobacteria and green chloroplasts form a coherent phylogenetic group but also suggest that the chloroplast lineage, which includes the cyanelle of C. paradoxa, is not just a sister group to the free-living forms but rather is contained within the cyanobacterial radiation.